Analysis of The Influence of Multiple Role Conflicts, Job Stress, and Self-Efficacy on Career Woman Performance at Dharmas Indonesia University - Hasibuan, Anggy Qurnia Ra'afy (UPI YPTK Journal of Business and Economics, 2024)
This study aims to analyze the impact of dual role conflict, work stress, and self-efficacy on the performance of career women at Dharmas Indonesia University. The population consists of women employees at Dharmas Indonesia University. Sampling technique by using total sampling. Data were collected through a survey of 104 respondents consisting of female lecturers and staff working at Dharmas Indonesia University. The study's results indicate that dual role conflict and work stress negatively impact career women's performance, while self-efficacy has a positive impact. The implications of this study highlight the importance of institutional support in managing dual roles and work stress to enhance the performance of career women.